2002
DOI: 10.1007/s10286-002-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and neurohumoral responses to head-up tilt in patients with chronic fatigue syndrome

Abstract: Head-up tilt evokes postural tachycardia or (pre)syncope in a minority of CFS patients. The observations in head-up tilt-negative CFS patients of a higher heart rate at baseline together with a marked decrease in stroke volume in response to head-up tilt may point to deconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 45 publications
7
24
0
Order By: Relevance
“…Survival analysis showed that CFS/POTS subjects and controls had similar subject dropout rates; thus, the incidence of presyncopal symptoms during graded tilt was similar between groups (see Figure 1). CFS/POTS subjects do not faint more often than controls, consistent with other studies describing syncope in adolescent/young adult CFS and/or POTS patients [10,4447]. …”
Section: Discussionsupporting
confidence: 90%
“…Survival analysis showed that CFS/POTS subjects and controls had similar subject dropout rates; thus, the incidence of presyncopal symptoms during graded tilt was similar between groups (see Figure 1). CFS/POTS subjects do not faint more often than controls, consistent with other studies describing syncope in adolescent/young adult CFS and/or POTS patients [10,4447]. …”
Section: Discussionsupporting
confidence: 90%
“…Hence subjects were not deliberately recruited with prevailing autonomic and cardiovascular symptoms. Indeed, the prevalence of such symptoms in the CFS cohort at study entry was comparable with that reported by other CFS studies [2,7,50,51]. Despite stringent matching procedures, which successfully controlled for numerous factors, the CFS cohort was older and more educated than the control subjects, necessitating statistical correction.…”
Section: Discussionsupporting
confidence: 77%
“…Both peripheral and autonomic neuropathy develop in vitamin B 12 deficiency, and treatment improves autonomic nervous system functions more rapidly. 31 Other studies have demonstrated that the change of posture may lead to an abnormal cardiovascular response (orthostatic hypotension, POTS, syncope) in one-third of patients 32,33 and that CFS is most likely associated with sympathetic dysfunction. 34 There are also studies supporting the similarity of the autonomic dysfunctions observed in CFS and POTS.…”
Section: Discussionmentioning
confidence: 99%